Increased mitophagy protects cochlear hair cells from aminoglycoside-induced damage. Issue 1 (2nd January 2023) - Zhang, Yuhua; Fang, Qiaojun; Wang, Hongfeng; Qi, Jieyu; Sun, Shan; Liao, Menghui; Wu, Yunhao; Hu, Yangnan; Jiang, Pei; Cheng, Cheng; Qian, Xiaoyun; Tang, Mingliang; et al.
ABSTRACT: Aminoglycosides exhibit ototoxicity by damaging mitochondria, which in turn generate reactive oxygen species that induce hair cell death and subsequent hearing loss. It is well known that damaged mitochondria are degraded by mitophagy, an important mitochondrial quality control system that maintains mitochondrial homeostasis and ensures cell survival. However, it is unclear whether dysregulation of mitophagy contributes to aminoglycoside-induced hair cell injury. In the current study, we found that PINK1-PRKN-mediated mitophagy was impaired in neomycin-treated hair cells. Our data suggested that mitochondrial recruitment of PRKN and phagophore recognition of damaged mitochondria during mitophagy were blocked following neomycin treatment. In addition, the degradation of damaged mitochondria by lysosomes was significantly decreased as indicated by the mitophagic flux reporter mt-mKeima. Moreover, we demonstrated that neomycin disrupted mitophagy through transcriptional inhibition of Pink1 expression, the key initiator of mitophagy. Moreover, we found that neomycin impaired mitophagy by inducing ATF3 expression. Importantly, treatment with a mitophagy activator could rescue neomycin-treated hair cells by increasing mitophagy, indicating that genetic modulation or drug intervention in mitophagy may have therapeutic potential for aminoglycoside-induced hearing loss. Abbreviations: AAV: adeno-associated virus; ABR: auditory brainstem response; ATF3: activating transcription factor 3; ATOH1/MATH1: atonal bHLH transcription factor 1; BafA1: bafilomycin A1 ; CCCP: carbonyl cyanide m-chlorophenyl hydrazone; COX4I1/COXIV: cytochrome c oxidase subunit 4I1; CTBP2/RIBEYE: C-terminal binding protein 2; DFP: deferiprone; EGFP: enhanced green fluorescent protein; FOXO3: forkhead box O3; GRIA2/GLUR2: glutamate receptor, ionotropic, AMPA2 (alpha 2); HC: hair cell; HSPD1/HSP60: heat shock protein 1 (chaperonin); IHC: inner hair cell; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; MYO7A: myosin VIIA; OPTN: optineurin; OMM: outer mitochondrial membrane; PRKN: parkin RBR E3 ubiquitin protein ligase; PINK1: PTEN induced putative kinase 1; RT-qPCR: real-time quantitative polymerase chain reaction; TOMM20/TOM20: translocase of outer mitochondrial membrane 20; TUNEL: Terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling; USP30: ubiquitin specific peptidase 30; XBP1: X-box binding protein 1.